Growth performance of Red Chittagong and Holstein crossbred bull calves using growth promoter (Journal of the Bangladesh Agricultural University, 2010)
The aim of the study was to evaluate and compare the effect of growth promoter 'Megavit-DB' on growth performance of indigenous Red Chittagong (RC) and Holstein Crossbred (HC) bull calves. For this purpose, six RC and six HC bull calves were assigned into four treatment groups having three calves in each as RCT0 (RC without Megavit-DB), RCT1 (RC with Megavit-DB), HCT0 (HC without Megavit-DB) and HCT1 (HC with Megavit-DB). The daily DM intake of different treatment groups were found almost similar. The daily average live weight gains were 0.27±0.05, 0.36±0.01, 0.36±0.01 and 0.45±0.05 kg/d, feed conversion efficiency were 9.08±0.16, 7.47±1.07, 7.13±1.24 and 6.16±0.27 and the average net returns (Tk.) were 1473.33±87, 2060±76.38, 1910±86.60 and 2776.67±44.10 for RCT0, RCT1, HCT0 and HCT1 treatment groups, respectively. The daily average live weight gain and feed conversion efficiency were significantly (p